2020
DOI: 10.3390/md18030144
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Research on the Bioactivity of Alginate Oligosaccharides

Abstract: Alginate is a natural polysaccharide present in various marine brown seaweeds. Alginate oligosaccharide (AOS) is a degradation product of alginate, which has received increasing attention due to its low molecular weight and promising biological activity. The wide-ranging biological activity of AOS is closely related to the diversity of their structures. AOS with a specific structure and distinct applications can be obtained by different methods of alginate degradation. This review focuses on recent advances in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 169 publications
(254 reference statements)
0
93
0
Order By: Relevance
“…Comparing the polysaccharides of terrestrial plant origin, seaweed polysaccharides constitute unique monomers like galactose, mannose, fucose, xylose etc. with varying degree of sulfation in their sugar residues [40] that influence the structure and biological properties of polymer isolated from each seaweed species [41]. This sulfate group of sugar moieties is found responsible for exhibiting anionic charge to the polymers [27,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the polysaccharides of terrestrial plant origin, seaweed polysaccharides constitute unique monomers like galactose, mannose, fucose, xylose etc. with varying degree of sulfation in their sugar residues [40] that influence the structure and biological properties of polymer isolated from each seaweed species [41]. This sulfate group of sugar moieties is found responsible for exhibiting anionic charge to the polymers [27,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…Chronic administration of D-gal may cause physiological states similar to those observed during natural aging, such as cell metabolism disorders and injury [ 12 ]. Alginate oligosaccharide (AOS) is a degradation product of alginate that has been extensively studied due to its wide range of pharmacological activities and beneficial effects [ 13 , 14 ]. Previous studies have shown that AOS has a variety of biological activities, such as antioxidant [ 15 ], antitumor [ 16 ], and immunomodulatory effects [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the mechanistic point, alginate has targeted oxidative pathways (e.g., ROS) and neuroinflammation (e.g., TLR4) to protect neuronal damages. So, regulation of GM and neuronal dysregulated pathways by alginate pave the road in attaining a promising gut-brain axis [ 203 ].…”
Section: Marine-derived Natural Products Against Diseases: Approacmentioning
confidence: 99%